Analysis of the Influence of Liquidity, Solvency and Probability on Financial Performance in Telecommunication Companies Listed on the Indonesia Stock Exchange for the 2018-2024 period - Zairin, Zairin; Diana, Diana (Hut Publication Business and Management, 2026)
The telecommunications sector in Indonesia has transformed into the backbone of the digital economy, but it faces major challenges in the form of cost structure pressures and significant fluctuations in the number of subscribers, especially the decline anomaly in 2022. This study aims to analyze the influence of Liquidity, Solvency, and Profitability on Financial Performance in telecommunication companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2024 period. The research method used is descriptive with a quantitative approach. The research sample was selected using a purposive sampling technique that resulted in four main companies: PT Telkom Indonesia Tbk, PT XL Axiata Tbk, PT Smartfren Telecom Tbk, and PT Indosat Ooredoo Hutchison Tbk. Data analysis techniques include classical assumption tests and multiple linear regression analysis using the SPSS program. The results of the study show that partially Liquidity has a significant and positive effect on Financial Performance (63,477 > table 1,703). Solvency has no significant effect on Financial Performance of 0.098 < table, indicating that the amount of debt does not directly determine the efficiency of the company's assets in this sector. Profitability has a significant effect on performance of -12,837 > table 1,703). Simultaneously, Liquidity, Solvency, and Profitability have a significant effect on Financial Performance with a Calculated value of 1415,550 > Factor 3.01. The value of the Coefficient of Determination r2 of 0.994 indicates that 99.4% of the variation in Financial Performance can be explained by these three variables, while the rest is influenced by other factors outside the model.